Regulation of MicroRNA-Mediated Developmental Changes by the SWR1 Chromatin Remodeling Complex. Issue 2 (18th April 2016) - Choi, Kyuha; Kim, Juhyun; Müller, Sebastian Y.; Oh, Mijin; Underwood, Charles; Henderson, Ian; Lee, Ilha
Abstract : SWR1-C is required for miRNA-mediated developmental controls through transcriptional activation and generates proper balances between miRNAs and target mRNAs for plant development in Arabidopsis thaliana. Abstract: The ATP-dependent SWR1 chromatin remodeling complex (SWR1-C) exchanges the histone H2A-H2B dimer with the H2A.Z-H2B dimer, producing variant nucleosomes. Arabidopsis thaliana SWR1-C contributes to the active transcription of many genes, but also to the repression of genes that respond to environmental and developmental stimuli. Unlike other higher eukaryotic H2A.Z deposition mutants (which are embryonically lethal), Arabidopsis SWR1-C component mutants, including arp6, survive and display a pleiotropic developmental phenotype. However, the molecular mechanisms of early flowering, leaf serration, and the production of extra petals in arp6 have not been completely elucidated. We report here that SWR1-C is required for miRNA-mediated developmental control via transcriptional regulation. In the mutants of the components of SWR1-C such as arp6, sef, and pie1, miR156 and miR164 levels are reduced at the transcriptional level, which results in the accumulation of target mRNAs and associated morphological changes. Sequencing of small RNA libraries confirmed that many miRNAs including miR156 decreased in arp6, though some miRNAs increased. The arp6 mutation suppresses the accumulation of not only unprocessed primary miRNAs, but also miRNA-regulated mRNAs in miRNA processing mutants, hyl1 and serrate, which suggests that arp6 has a transcriptional effect on both miRNAs and their targets. We consistently detected that the arp6 mutant exhibits increased nucleosome occupancy at the tested MIR gene promoters, indicating that SWR1-C contributes to transcriptional activation via nucleosome dynamics. Our findings suggest that SWR1-C contributes to the fine control of plant development by generating a balance between miRNAs and target mRNAs at the transcriptional level.